Search for Wγ Resonances in Proton-Proton Collisions at S=13 TeV Using Hadronic Decays of Lorentz-Boosted W Bosons - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Erö, J.; Alves, G.A. (Elsevier B.V., 2022)
A search for Wγ resonances in the mass range between 0.7 and 6.0 TeV is presented. The W boson is reconstructed via its hadronic decays, with the final-state products forming a single large-radius jet, owing to a high Lorentz boost of the W boson. The search is based on proton-proton collision data at s=13 TeV, corresponding to an integrated luminosity of 137 fb−1, collected with the CMS detector at the LHC in 2016–2018. The Wγ mass spectrum is parameterized with a smoothly falling background function and examined for the presence of resonance-like signals. No significant excess above the predicted background is observed. Model-specific upper limits at 95% confidence level on the product of the cross section and branching fraction to the Wγ channel are set. Limits for narrow resonances and for resonances with an intrinsic width equal to 5% of their mass, for spin-0 and spin-1 hypotheses, range between 0.17 fb at 6.0 TeV and 55 fb at 0.7 TeV. These are the most restrictive limits to date on the existence of such resonances over a large range of probed masses. In specific heavy scalar (vector) triplet benchmark models, narrow resonances with masses between 0.75 (1.15) and 1.40 (1.36) TeV are excluded for a range of model parameters. Model-independent limits on the product of the cross section, signal acceptance, and branching fraction to the Wγ channel are set for minimum Wγ mass thresholds between 1.5 and 8.0 TeV. © 2022 The Author(s)
Keywords: BSM Particles; CMS; Wγ Resonances